Impact of Soil Disinfestation on Fungal and Bacterial Communities in Soil With Cucumber Cultivation - Wang, Yan; Jin, Yujie; Han, Ping; Hao, Jianjun; Pan, Hongyu; Liu, Jinliang (Frontiers in Microbiology, 2021)
Soil treatment with disinfectants has been used for controlling soilborne phytopathogens. Besides suppressing specific pathogens, how these disinfectants impact soil health, especially soil microbial communities, is yet to be systemically determined. The objectives of this study were to examine the effects of three representative disinfectants, including the dazomet fumigant, fenaminosulf fungicide, and kasugamycin antibiotic on chemical properties, enzymatic activities, and microbial communities in soil for cucumber cultivation. Results showed that 14 days after soil treatment with these chemicals, residual content of dazomet and kasugamycin quickly declined in soil and were undetectable, while fenaminosulf residues were found at 0.48 ± 0.01 mg/kg. Total nitrogen and total carbon increased in soil after dazomet treatment. Urease and sucrase activities were significantly restrained after disinfectant application. The disinfectants did not significantly change the taxon of predominant bacteria and fungi but altered the relative abundance and diversity of soil microbiome, as well as microbial interspecific relationships. Moreover, cucumber cultivation enhanced the overall soil microbial diversity and enzymatic activities, which diminished the difference of soil microbiome among four treatments. The difference in soil microbial diversity among the four treatments became smaller after planting cucumber. Thus, soil microbial communities were affected by soil disinfectants and gradually recovered by cucumber application.